ANALISIS MINAT SISWA SISWI SMP/MTS TERHADAP EKSTRAKURIKULER MA MUHAMMADIYAH 1 PONOROGO MENGGUNAKAN METODE ASSOCIATION RULES BERBASIS WEB - Muh Ardiansyah; Indah Puji Astuti; Ghulam Asrofi Buntoro (KOMPUTEK, 2022)
Currently, the world of education must be managed professionally, because of the increasingly fierce competition in education today. Educational institutions will be abandoned by the community if they are managed poorly. MA Muhammadiyah 1 Ponorogo School is one of the private schools owned by the Muhammadiyah business charity in Ponorogo district. MA Muhammadiyah 1 Ponorogo has a small number of students, due to the lack of student interest in entering the school. To find out that students are interested in entering MA Muhammadyah 1 Ponorogo, the school made a new breakthrough that could attract students to register there. To find out, the researchers used data mining techniques with the Apriori Algorithm method, and supported by the Apriori web browser system by examining student extracurricular interest data with 177 respondents with 47 extracurriculars. Data Mining is a combination of data analysis techniques, while Apriori Algorithm is a method which is most often used because it is very simple, easy and the most widely proposed by several researchers, because there are two parameters, namely Support and Confidence. So the results of the” research predictions obtained are that the most popular extracurriculars for junior high school/MTs students are futsal and volleyball with a minimum value of support = 11% and a minimum value of confidence = 52%.